(3GdcJGH GdefaP Ydi jO SQGjGs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3CWGd Gddg HbGA GdTjN GdNjQ GdaGVd hCOGe JCjjOg hfYeJg hMQS ef GdZjQ KbJg hfjJg hbO Yde COGe Gddg SYGOJg Cfg NQL ef YfOfG HGdHVGYI s
(3BNQgG (B:s
(3aeTQa Ydi cd NjQ ef GdRjGOI hGdHQcI hGdCef hbO hUd EdjfG Cf UdjI CNPhgG GdQhe aGddg jHWd Pdc hdG jLYdg ef UMjM hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B90s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis